Analisis Hukum Wanprestasi Perusahaan Asuransi Jiwa Terhadap Nasabah Pemegang Polis Dalam Perspektif Perlindungan Konsumen - Suharni Tiur Mita Simarmata; Atika Sunarto; Muhammad Ali Adnan (Fakultas Hukum, Universitas Warmadewa, 2026)
Indonesia's life insurance industry has experienced significant growth, yet default practices still occur that harm policyholders through claim rejections, payment delays, payments not matching policy values, and unilateral contract terminations. This phenomenon violates contract law principles and threatens public trust in the insurance industry. This research aims to analyze forms of life insurance company defaults, identify legal protection for customers, and examine causal factors of defaults. This normative legal research uses statute, conceptual, and case approaches with data from library research analyzed qualitatively. Results show defaults manifest in four forms violating pacta sunt servanda and utmost good faith principles. Legal protection is classified into preventive through Financial Services Authority regulations and supervision, and repressive through dispute resolution mechanisms and compensation rights, though effectiveness is constrained by procedural complexity and weak sanction enforcement. Causal factors include internal factors of unhealthy financial management, weak Good Corporate Governance, and profit-oriented culture, plus external factors of sub-optimal supervision, low public financial literacy, and unstable economic conditions.